Bioeconomy, productivity and sustainability. Case study of the Faroe Islands - Johannessen, Birgit, 1983- (2014)
As the pressure on the world renewable biological resources grows, the focus on the bioeconomy gets more and more important. The purpose of this thesis is to gain an in depth understanding of exactly what a bioeconomy is. In order to gain the in depth knowledge required for the thesis a case study methodology will be utilized to map the renewable biological resources available in the Faroe Islands as well as economic activities. Also some productivity measures will be discussed along with sustainability. The willingness to make the transition to a bioeconomy is evident, but there are still barriers.